Determinant of Residential Property Price Index in Five Asian Emerging Market Countries : A Demand and Supply Approach - Silma Fikria Balqis, - (International Journal of Social Science and Economics Invention, 2021)
This study aims to analyze the factors influencing the Residential Property Price Index (RPPI) from the demand and supply sides in five Asian emerging market countries. The data used are semi-annual data from the first semester of 2009 until the second semester of 2019 because this study aims to denote the impact of RPPI toward the demand and supply indicators after the global crisis in 2008. The dependent variable of this study is the RPPI, while the independent variables include the number of workers, real interest rate, economic growth, and the Real Effective Exchange Rate (REER). The Fixed Effects Model (FEM) is thus the applied method to process the data. In the end, the results indicate that all independent variables are significant toward the RPPI. The number of workers, real interest rate, and REER negatively affect the RPPI, while economic growth positively affects the RPPI.